Identifying potentially attractive publications in a digital library which remain invisible to users - Catlow, John; Górny, Mirosław; Lewandowski, Rafał (Qualitative and Quantitative Methods in Libraries, 2019)
Digital library collections contain publications of different degrees of attractiveness to users. However, some publications belonging to categories that are generally sought by users appear to be “invisible”. The Digital Library of Wielkopolska has implemented a method enabling such items to be identified. This involves monitoring the average daily numbers of views of individual publications available in the library. Among the 100 most frequently accessed items, certain categories are seen to be well represented; these indicate the types of publications which are most popular among users. The lowest daily rate of views among these 100 items is taken as a threshold for visibility. If a publication belongs to one of the popular categories, but its average daily number of views is below this threshold, it may be classified as a “lost” item. It is then necessary to determine the reason for this. The cause is usually the inadequacy of the information contained in the item’s description.